Gut-derived endotoxin stimulates factor VIII secretion from endothelial cells. Implications for hypercoagulability in cirrhosis - Carnevale, Roberto; Raparelli, Valeria; Nocella, Cristina; Bartimoccia, Simona; Novo, Marta; Severino, Anna; De Falco, Elena; Cammisotto, Vittoria; Pasquale, Chiara; Crescioli, Clara; Scavalli, Antonio Sili; Riggio, Oliviero; et al. (Journal of hepatology, 2017)
[Display omitted] •Cirrhosis is associated with thrombosis in portal and systemic circulation.•Cirrhosis display a concomitant increase of factor VIII and LPS from E. Coli.•LPS contributes to release factor VIII from endothelial cells. Patients with cirrhosis display enhanced blood levels of factor VIII, which may result in harmful activation of the clotting system; however, the underlying mechanism is unknown. We performed a cross-sectional study in patients with cirrhosis (n=61) and matched controls (n=61) comparing blood levels of factor VIII, von Willebrand factor (vWf), lipopolysaccharide (LPS) and positivity for Escherichia coli DNA. Furthermore, we performed an in vitro study to investigate if LPS, in a concentration range similar to that found in the peripheral circulation of cirrhotic patients, was able to elicit factor VIII secretion from human umbilical vein endothelial cells (HUVEC). Patients with cirrhosis displayed higher serum levels of LPS (55.8 [42.2–79.9] vs. 23.0 [7.0–34.0]pg/ml, p<0.001), factor VIII (172.0 [130.0–278.0] vs. 39.0 [26.0–47.0]U/dl, p<0.0001), vWf (265.0 [185.0–366.0] vs. 57.0 [48.0–65.0]U/dl, p<0.001) and positivity for Escherichia coli DNA (88% vs. 3%, p<0.001, n=34) compared to controls. Serum LPS correlated significantly with factor VIII (r=0.80, p<0.001) and vWf (r=0.63, p<0.001). Only LPS (beta-coefficient=0.70, p<0.0001) independently predicted factor VIII levels. The in vitro study showed that LPS provoked factor VIII and vWf release from HUVEC via formation and secretion of Weibel-Palade bodies, a phenomenon blunted by pre-treating HUVEC with an inhibitor of Toll-like receptor 4. The study provides the first evidence that LPS derived from gut microbiota increases the systemic levels of factor VIII via stimulating its release by endothelial cells. Lay summary: Cirrhosis is associated with thrombosis in portal and systemic circulation. Enhanced levels of factor VIII have been suggested to play a role but the underlying mechanism is still unclear. Here we show that patients with cirrhosis display a concomitant increase of factor VIII and lipopolysaccharide (LPS) from Escherichia coli and suggest that LPS contributes to the release of factor VIII from endothelial cells.